Toward Understanding of Quiet Human Resource Management Theory in Iranian Organizations: Theoretical Origins, Conceptual Narration and its Consequences - Abbas Nargesian; Sajjad Sadpoor (مدیریت دولتی)
ObjectiveThe concept of "quiet" human resource management (HRM) has gained significant attention in recent years, particularly in response to the pervasive hustle culture and competitive organizational landscapes exacerbated by challenging economic conditions. Quiet HRM refers to subtle practices that impact employees' job status, often without overt communication or transparency. As the prevalence of quiet HRM concepts increases, their implications for organizational dynamics are profound and far-reaching. This study aims to establish a theoretical framework that describes and explains the emerging phenomenon of quiet HRM within Iranian organizations.MethodsThis research was conducted within an interpretive philosophical paradigm, utilizing semi-structured interviews to uncover the core dimensions and components of quiet HRM. A total of 22 experts from companies affiliated with the National Iranian Copper Industries Company participated in the study. The research employed a purposive sampling technique, specifically theoretical sampling, consistent with the Strauss and Corbin grounded theory approach. To ensure the rigor of the study, credibility indicators specific to grounded theory were used to assess the quality of the research.ResultsThrough the application of Strauss and Corbin's grounded theory methodology, the study identified several subcategories and conceptual categories during the open coding stage. In the axial coding stage, these categories were organized into a paradigmatic model, which included causal conditions, strategy, contextual conditions, intervening conditions, and consequences. The selective coding stage involved the introduction and elaboration of the theory derived from the data, providing a comprehensive understanding of quiet HRM practices.ConclusionQuiet HRM encompasses various dimensions, including quiet firing, quitting, hiring, promotion, and performance evaluation. These practices often stem from individual factors such as superior employee skills and performance, job-related factors like stress and burnout, and organizational factors including cost-saving measures and workforce restructuring. Quiet HRM tends to emerge under exploitative leadership and a hard HRM approach, particularly in environments characterized by organizational ambiguity, discriminatory cultures, and economic hardship. However, transparency, organizational justice, quiet leadership, a soft HRM approach, and employee-driven job re-creation can mitigate these practices. The consequences of quiet HRM are both positive, such as skill diversification and identification of high performers, and negative, including increased turnover, damage to employer branding, and declines in employee mental health, job satisfaction, and performance. The findings of this study offer critical insights for management practitioners navigating the complexities of quiet HRM. By understanding the underlying factors that contribute to quiet HRM practices, organizations can implement strategies to reduce their negative effects and foster a more transparent, just, and supportive work environment. Management professionals can thereby promote an ethical, employee-centric approach to HRM, contributing to a healthier, more productive, and sustainable organizational culture. Future research should explore the causes and consequences of quiet HRM in diverse organizational settings, with in-depth studies in specific geographical contexts providing valuable insights for HRM policymakers.